(3HjGf Gdhge hGdEjgGe GdhGbYjf aj cJGH GdGMcGes - (3Ydj Hf eMeO Hf YHO Gdedc GdcJGej GdMejQj GdaGSj, CHh GdMSf GHf GdbWGf,J (B628 (3g` s; (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ceG jMb dg hjLH hHYO aEf CHG eMeO GdCROi hHEYJHGQ gPjf GdbSejf ef GdChgGe hGdEHgGeGJ s
(3BNQgG (B:s
(3jfJgi HGdMOjK GdTQja (B" (3dcd Ojf Ndb hNdb GdESdGe GdMjGA ef dGMjGA dg dGOjf dg (B" (3Hbhdg hEfeG cJHJg cfHMK Yf adYdg eYQha cd GdSaQ GdChd s
(3GdfSNI HgG MhGTs
(3ef JMHjS hGdOI CHh GdYHGS GdefUhQ HJGQjN (B1011s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdeGdcjs